An 83‐year‐old patient with RET fusion‐positive non‐small cell lung cancer experiencing severe hepatic disorder due to selpercatinib administration. Issue 5 (9th April 2023) - Nakashima, Kazuhisa; Mitarai, Yuki; Tanaka, Seiko; Nakao, Mika; Okuno, Takae; Okimoto, Tamio; Tanabe, Ryo; Yanagawa, Takashi; Tsubata, Yukari; Isobe, Takeshi
Abstract: An 83‐year‐old woman with RET fusion‐positive advanced lung adenocarcinoma was administered selpercatinib 320 mg/day. Despite the shrinking of the tumour, fever, fatigue, and anorexia developed on day 17. Selpercatinib administration was interrupted. On day 21, elevated blood aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were observed. On day 28, AST and ALT levels increased to demonstrate Grade 4 in CTCAE Ver.5. The patient received a glycyrrhizin‐compounding agent and steroid treatment, and AST and ALT levels gradually decreased. On day 63, selpercatinib 160 mg/day was restarted after improvement of the hepatic disorder. Since then, selpercatinib was continued without any severe adverse events. Selpercatinib is a reasonable treatment option for RET fusion‐positive advanced non‐small cell lung cancer even in older patients. However, old age may be a risk factor for adverse events including hepatic disorders. For safe treatment in such patients, careful follow‐up is required. Abstract : The efficacy and safety of selpercatinib in older patients remain unclear. We report a case of an old female patient with RET fusion‐positive NSCLC who experienced severe hepatic disorder caused by selpercatinib.